Development and Validation of the Muslim Prayer Ability Scale (MPAS) Among Patients’ With Diabetic Foot Problem - Mohd Yusof, Nazri; Musa, Ramli; Mohamad, Hasbullah (universiti putera malaysia, 2022)
Introduction: The available tools to assess the ability of Muslim patients to pray were develop by the rehabilitation therapist to assist Muslim patients in performing prayer and only focussing physical domain. It was not design to be used by the treating doctors as a method to decide and monitor progress of disease and treatment. The objective of this study is to design and validate a more holistic scale that can measure Muslim ability to perform their daily prayer Method: For scale construction, five experts from back grounds of orthopaedic, psychiatry, Islamic knowledge and Islamic philosophy of science were gathered to construct the domains and items for the new scale. The preliminary of 23 item-scale was then administered to 212 individuals (87 among patients with diabetic foot problem and 125 from the control group) in 2 public hospitals in Kuantan using cross-sectional study method. Reliability is measured using Cronbach’s alpha and the construct validity is measured using the exploratory factor analysis. Statistical analysis is done using SPSS version 24. Results: The Muslim prayer ability scale (MPAS) has a good reliability with Cronbach’s alpha value of 0.79. Based on Construct validation analyses and factor loadings, we established a 19-item scale to measure the ability of Muslim with three items in each domain. All of the items showed good factor loadings of more than 0.5. The 5 identified domains are namely Preparation of praying, Physical movement, Spirituality, Cognitive & Tayammum and Disturbance. The MPAS also has a good criterion validity with 85% sensitivity and 93% specificity in predicting the ability of patients with diabetic foot problem to perform prayer. Conclusion: This study proved that the new MPAS is valid and reliable to be used as tools to measure prayer ability in Muslim patients with diabetic foot problem.